New demands for primary health care in Brazil: palliative care - de Paula Paz, Cássia Regina; Dias Reis Pessalacia, Juliana; Campos Pavone Zoboli, Elma Lourdes; de Souza, Hieda Ludugério; Ferreira Granja, Gabriela; Cabral Schveitzer, Mariana (Investigación y Educación en Enfermería, 2016)
Objective. Assess the need for incorporation of palliative care in primary health care (PHC) through the characterization of users eligible for this type of care, enrolled in a program for devices dispensing. Methods. Descriptive study of case series conducted in 14 health units in São Paulo (Brazil) in 2012. It was included medical records of those enrolled in a program for users with urinary and fecal incontinence, and it was applied Karnofsky Performance Scale Index (KPS) to identify the indication of palliative care. Results. 141 of the 160 selected medical records had KPS information. Most cases (98.3%, 138/141) had performance below 70% and, therefore, patients were eligible for palliative care. The most frequent pathologies was related to chronic degenerative diseases (46.3%), followed by disorders related to quality of care during pregnancy and childbirth (24.38%). Conclusion. It is necessary to include palliative care in PHC in order to provide comprehensive, shared and humanized care to patients who need this. How to cite this article: Paz CRP, Pessalacia JDR, Zoboli ELCP, Souza HL, Granja GF, Schveitzer MC. New demands for primary health care in Brazil: palliative care. Invest Educ Enferm. 2016; 34(1): 46-57